Metabolic engineering of Corynebacterium glutamicum for L-tyrosine production from glucose and xylose - SARIYAR AKBULUT, BERNA (My University, 2023)
© 2023 Elsevier B.V.Microbial production of aromatic compounds is an attractive and sustainable biotechnological approach. With this motivation, here metabolic engineering of Corynebacterium glutamicum for L-tyrosine (L-Tyr) overproduction was attempted by pushing the carbon flux more towards L-Tyr. Translational start codon exchanges of prephenate dehydratase (pheA), anthranilate synthase (trpE), and phenylalanine aminotransferase (pat) genes revealed that reduced expression of pheA was the major contributor to increased L-Tyr titer while codon exchange in trpE was effective to a lower extent. Overexpression of aroE and qsuC, encoding shikimate dehydrogenase and 3-dehydroquinate dehydratase, respectively, and of dapC (cg1253), which is predicted to encode prephenate aminotransferase, were futile to increase L-Tyr titer. Similarly, deletion of the qsuABD gene cluster had also not enhanced titer. As for increasing precursor supply, deletion of ptsG of glucose uptake and overexpression of inositol permease (iolT2) and glucokinase (glcK) were not effective, but with utilization of xylose, enabled by overexpression of xylose isomerase (xylA) and xylulokinase (xylB), titer improved. Highest L-Tyr titer using the construct was 3.1 g/L on glucose and 3.6 g/L on a 1:3 (w/v) mixture of glucose and xylose. This result displays the potential of the constructed strain to produce L-Tyr from lignocellulosic renewable carbon sources.
Keywords: Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Life Sciences; Biotechnology; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Mühendislik; Mikrobiyoloji; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); ENGINEERING; MICROBIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Uygulamalı Mikrobiyoloji ve Biyoteknoloji; Bioengineering; Physical Sciences; Applied Microbiology and Biotechnology; Corynebacterium glutamicum; L-Tyrosine overproduction; Rational design; Sustainable process